Soluble carbohydrate content variation in Sanionia uncinata and Polytrichastrum alpinum, two Antarctic mosses with contrasting desiccation capacities - Zúñiga-González,Paz (Sociedad de Biología de Chile, 2016)
BACKGROUND: Cryptogamic vegetation dominates the ice-free areas along the Antarctic Peninsula. The two mosses Sanionia uncinata and Polytrichastrum alpinum inhabit soils with contrasting water availability. Sanionia uncinata grows in soil with continuous water supply, while P. alpinum grows in sandy, non-flooded soils. Desiccation and rehydration experiments were carried out to test for differences in the rate of water loss and uptake, with non-structural carbohydrates analysed to test their role in these processes. RESULTS: Individual plants of S. uncinata lost water 60 % faster than P. alpinum; however, clumps of S. uncinata took longer to dry than those of P. alpinum (11 vs. 5 h, respectively). In contrast, rehydration took less than 10 min for both mosses. Total non-structural carbohydrate content was higher in P. alpinum than in S. uncinata, but sugar levels changed more in P. alpinum during desiccation and rehydration (60-50 %) when compared to S. uncinata. We report the presence of galactinol (a precursor of the raffinose family) for the first time in P. alpinum. Galactinol was present at higher amounts than all other non-structural sugars. CONCLUSIONS: Individual plants of S. uncinata were not able to retain water for long periods but by growing and forming carpets, this species can retain water the longest. In contrast individual P. alpinum plants required more time to lose water than S. uncinata, but as moss cushions they suffered desiccation faster than the later. On the other hand, both species rehydrated very quickly. We found that when both mosses lost 50 % of their water, carbohydrates content remained stable and the plants did not accumulate non-structural carbohydrates during the desiccation prosses as usually occurs in vascular plants. The raffinose family oligosaccarides decreased during desiccation, and increased during rehydration, suggesting they function as osmoprotectors.